2008
DOI: 10.1097/mco.0b013e3282f2b0ad
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone, arginine and exercise

Abstract: Exercise is a very potent stimulator of growth hormone release and there is considerable research documenting the dramatic growth hormone rise. At rest oral L-arginine ingestion will enhance the growth hormone response and the combination of arginine plus exercise increases growth hormone, but this increase may be less than seen with exercise alone. This diminished response is seen in both in both younger and older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…More recently, in 2008, a review by Kanaley [10] concluded that studies have shown that resting growth hormone responses increase with oral ingestion of L-arginine and the dose range is 5-9 g of arginine [13]. This review also indicated that exercise alone is the more potent stimulator of growth hormone response regardless of age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, in 2008, a review by Kanaley [10] concluded that studies have shown that resting growth hormone responses increase with oral ingestion of L-arginine and the dose range is 5-9 g of arginine [13]. This review also indicated that exercise alone is the more potent stimulator of growth hormone response regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies were done with competitive weightlifters who have been given arginine with another amino acid or a placebo [10,11]. Insulin levels and hGH were measured daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginine has been shown to support protein synthesis, improve nitrogen balance and support wound healing. [9][10][11] There is a theory that consuming arginine will raise the blood level of human growth hormone (hGH) and insulin. The performance advantage would be that increases in these two hormones (hGH and insulin) would help build more body mass by natural growth (accretion) and the decrease of body fat.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine has been shown to support protein synthesis, improve nitrogen balance and support wound healing. [9][10][11] There is a theory that consuming arginine will raise the blood level of human growth hormone (hGH) and insulin. …”
mentioning
confidence: 99%